2021
DOI: 10.1007/s00520-021-06221-w
|View full text |Cite
|
Sign up to set email alerts
|

Recall, perceptions and determinants of receiving physical activity advice amongst cancer survivors: a mixed-methods survey

Abstract: Purpose This study explored cancer survivors’ views and experiences of receiving physical activity advice post-diagnosis. We also determined the influence of sociodemographic characteristics on the recall of physical activity advice and whether receiving advice was associated with meeting physical activity guidelines. Methods An anonymised, mixed-methods, 27-item survey was distributed to cancer survivors via online cancer communities in the UK. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
(58 reference statements)
0
2
0
Order By: Relevance
“… 86 Other factors highlighted in the literature that influence adherence to surveillance, healthcare and health-behaviour recommendations include younger age at diagnosis, higher education level, 87 clear patient-provider discussion on risks and needs, 76 , 81 , 88 a greater awareness of the benefits and barriers to care, 89 and perceived appropriateness of the information relative to the survivors’ treatment stage and general state of health. 90 This complex array of socio-demographic and clinical factors influencing survivors’ adherence to recommendations underscores the importance of providing tailored survivorship care for each survivor and the indispensable role of communication between the clinic, survivor and their PCP. Further research is necessary to understand whether greater adherence is more achievable in the long-term and to evaluate longitudinal predictors of adherence during the survivorship period.…”
Section: Discussionmentioning
confidence: 99%
“… 86 Other factors highlighted in the literature that influence adherence to surveillance, healthcare and health-behaviour recommendations include younger age at diagnosis, higher education level, 87 clear patient-provider discussion on risks and needs, 76 , 81 , 88 a greater awareness of the benefits and barriers to care, 89 and perceived appropriateness of the information relative to the survivors’ treatment stage and general state of health. 90 This complex array of socio-demographic and clinical factors influencing survivors’ adherence to recommendations underscores the importance of providing tailored survivorship care for each survivor and the indispensable role of communication between the clinic, survivor and their PCP. Further research is necessary to understand whether greater adherence is more achievable in the long-term and to evaluate longitudinal predictors of adherence during the survivorship period.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Cancer survivors also report wanting more guidance on the type, frequency, intensity and duration of exercise they can safely undertake. 20 'Telehealth exercise' allows patients to exercise at home under the 'virtual' supervision of an exercise instructor. The instructor guides patients through the exercises in real time, mimicking the delivery of traditional facilitybased training without the need for travel or access to facilities.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Furthermore, 31% of patients in the UK reported being inactive during and after treatment (i.e. completed less than 30 min of moderate-intensity activity a week) [ 12 ] and 43% of patients reported becoming less active following their diagnosis [ 13 ]. Previous qualitative research with cancer clinicians reported several barriers to the implementation of physical activity advice in routine care, which included a lack of training and knowledge on how to do so [ 14 ], time, concerns regarding patient safety [ 15 , 16 ] and lack of accessible patient referral pathways to exercise/physical activity specialists [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%